PENGARUH TINGGINYA KADAR GULA DARAH TERHADAP KEJADIAN KATARAK PADA PASIEN DIABETES MELLITUS DI BALAI KESEHATAN MATA MASYARAKAT SULAWESI SELATAN TAHUN 2014 - Nur Hikma M.Jihad; Rahasia Taufik; Nurmila Nurmila (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2018)
In order to detect the occurrence of shock in dengue patients is difficult. Decrease in platelet levels and increased levels of hematocrit is often used as an indicator of dengue especially in the event of shock. Leukocyte levels to see whether there is leukopenia or leukocytosis. By checking levels that may help in early treatment of shock. To determine the relationship between blood platelets, hematocrit and leukocytes in patients with dengue hemorrhagic fever (DHF) and shock. The study observational analytic cross-sectional retrospective design. Samples were DHF patients who received inpatient services at the hospital. RS. Faisal, Baji Labuang RS and RS. Haji in 2011-2012 taken by using total sampling. Data were obtained from medical records and analyzed by Chi Square test. The number of samples involved in this study were 100 cases. Most samples were children aged 5-15 years 54 people (54.0%), male sex by the number of 52 people (52.0%). The degree of the highest degree DHF III 40 people (40.0%). As well as the many levels of platelets were thrombocytopenia (100,000 / p l) by 55 people (55.0%), most were rising hematocrit levels than normal (36%), as well as the highest levels of leukocyte levels are still normal 55 people (55,0%). In this study the results obtained Chi Square statistical test platelet levels there is a significant relationship between shock DHF and shock (p =0.003), whereas the hematocrit levels showed different results there is no significant relationship between shock DHF and shock (p =0.067) and leukocyte levels show different results there is no significant relationship between shock DHF and shock (p =0.841).